Getting and spending - "Roche, John Ward" (London, 1963)
Economics is the study of the principles that determine the allocation of scarce resources between the alternative uses they can satisfy. This is "the economic problem" of all human societies and it will remain until superabundance replaces scarcity and removes the need for allocation. It is common to under-developed and developed countries, agricultural and industrial communities, communist and capitalist societies. It is the purpose of this book to explain the principles of allocation in simple terms for the beginner.
Keywords: Economics